Association of body mass index and fasting plasma glucose concentration with post-transplantation diabetes mellitus in Chinese heart transplant recipients. Issue 3 (March 2020) - Zhao, Tian; Zhao, Yinan; Zong, Ailun; Tang, Yadi; Shi, Xiaopeng; Zhou, Yingsheng
Objective: Post-transplantation diabetes mellitus (PTDM) is a frequent complication after heart transplantation. We investigated the specific predictors of PTDM in Chinese heart transplant recipients and the prognostic value of these predictors. Methods: We retrospectively analyzed 122 adult patients who underwent heart transplantation. Comparisons were made between patients with PTDM (n = 44) and those without PTDM (n = 78). Results: During the median follow-up of 44 months, the cumulative incidence of PTDM was 19.7% at 1 year after transplantation and 36.1% at the endpoint. PTDM was associated with a significantly higher preoperative body mass index (BMI) (odds ratio [OR] = 1.349), fasting plasma glucose (FPG) concentration (OR = 2.538), and serum uric acid concentration (OR = 1.005) after transplantation. The area under the receiver operating characteristic curve was 0.708 and 0.763 for the BMI and FPG concentration, respectively. The incidence of acute rejection and infection were higher and the all-cause mortality rate was considerably greater in patients with than without PTDM. Conclusions: A higher preoperative BMI (>23 kg/m 2 ), FPG concentration (>5.2 mmol/L), and uric acid concentration could potentially predict PTDM in Chinese heart transplant recipients. PTDM influences long-term survival after heart transplantation.